Childhood and adolescence of a Latin American translator, or about José Coronel Urtecho’s training - Raimondi, Sergio (Universidad Nacional del Litoral, 2019)
How does someone become a translator? What is his bond to languages other than the mother tongue? Is there a relationship between learning those languages and learning their literatures? Which language is learned when a language is learned? Questions like these emerge from the reading of the chronicle «El americanismo en la casa de mi abuelo» (1962), in which it is possible to see how the «destiny-of-translation» of the Nicaraguan José Coronel Urtecho occurs in the years prior to his trip to San Francisco, US, in 1924.